Upaya pelestarian budaya Sasak melalui Bale Sangkep di Desa Barabali - Raehanah, Raehanah; Susilawati, Esa; Rahman Budiman, Dendi (State Islamic University of Mataram, 2023)
The culture in Lombok cannot be separated from influences from Java and Bali. The service is carried out as a form of participation in the introduction and preservation of culture in Barabali Village. One of the efforts made to facilitate the preservation of culture in the village of Barabali is the establishment of Bale Sangkep. This building is used as a place to hold village meetings and traditional schools. Traditional schools teach the community, especially the younger generation, the Sanskrit language, sasak songs, and the Merariq tradition that applies in Barabali Village. The regular use of Bale Sangkep begins in 2020. With this Bale Sangkep, the younger generation can better understand the traditions that exist in society. Based on the interviews and activity participation at Bale Sangkep, efforts that can be made to preserve the customs that have been handed down from the ancestors include: 1) traditional schools, 2) use of Bale Sangkep, 3) active participation of the community, 4) development of insight, 5 ) application in daily life, 6) collaboration between generations, and 7) respect for cultural figures..